Young coronary artery disease in patients undergoing percutaneous coronary intervention - Zuhdi, A.S.; Mariapun, J.; Hairi, N.N.; Ahmad, W.A.W.; Abidin, I.Z.; Undok, A.W.; Ismail, M.D.; Sim, K.H. (Medknow Publications, 2013)
BACKGROUND AND OBJECTIVES: Understanding the nature and pattern of young coronary artery disease (CAD) is important due to the tremendous impact on these patients' socio-economic and physical aspect. Data on young CAD in the southeast Asian region is rather patchy and limited. Hence we utilized our National Cardiovascular Disease Database (NCVD)-Percutaneous Coronary Intervention (PCI) Registry to analyze young patients who underwent PCI in the year 2007 to 2009.